Altered expression of schizophrenia-related genes in mice lacking mGlu5 receptors - Luoni, Alessia; Gass, Peter; Brambilla, Paolo; Ruggeri, Mirella; Riva, Marco A.; Inta, Dragos (European archives of psychiatry and clinical neuroscience, 2018)
The evidence underlying the so-called glutamatergic hypothesis ranges from NMDA receptor hypofunction to an imbalance between excitatory and inhibitory circuits in specific brain structures. Among all glutamatergic system components, metabotropic receptors play a main role in regulating neuronal excitability and synaptic plasticity. Here, we investigated, using qRT-PCR and western blot, consequences in the hippocampus and prefrontal/frontal cortex (PFC/FC) of mice with a genetic deletion of the metabotropic glutamate receptor 5 (mGlu5), addressing key components of the GABAergic and glutamatergic systems. We found that mGlu5 knockout (KO) mice showed a significant reduction of reelin, GAD65, GAD67 and parvalbumin mRNA levels, which is specific for the PFC/FC, and that is paralleled by a significant reduction of protein levels in male KO mice. We next analyzed the main NMDA and AMPA receptor subunits, namely GluN1, GluN2A, GluN2B and GluA1, and we found that mGlu5 deletion determined a significant reduction of their mRNA levels, also within the hippocampus, with differences between the two genders. Our data suggest that neurochemical abnormalities impinging the glutamatergic and GABAergic systems may be responsible for the behavioral phenotype associated with mGlu5 KO animals and point to the close interaction of these molecular players for the development of neuropsychiatric disorders such as schizophrenia. These data could contribute to a better understanding of the involvement of mGlu5 alterations in the molecular imbalance between excitation and inhibition underlying the emergence of a schizophrenic-like phenotype and to understand the potential of mGlu5 modulators in reversing the deficits characterizing the schizophrenic pathology.
Gesehen am 2907.2019